The Foundation of Peace Education by Jan Amos Comenius (1592-1670) and its Topicality - Reinhard Golz (International Dialogues on Education: Past and Present, 2015)
The foundation of a peace education was an integral part of the pansophic work of J.A. Comenius (1592-1670), a consequence of his own life experiences as a refugee, displaced persons and asylum seeker during the Thirty Years’ War (1618-1648). As an educator, theologian, philosopher and linguist, Comenius significantly contributed to the reconciliation of peoples, cultures and religions. He can thus be seen as the founder of an intercultural, international and inter-religious peace education, whose growing importance in our times is obvious. Cultural and religious differences multiply in the wake of growing social problems. There is new relevance in acquiring the Comenian concept of intercultural and interreligious dialogue and peace education in the context of current general-xenophobic, racist and especially Islamophobic trends in parts of the German and European populations. Peace education must expose anti-humanist, xenophobic positions and educate on the benefits of cosmopolitan societies.